Precise orbit determination of GNSS satellites using microwave and laser ranging data - Bury, Grzegorz (Wyznaczanie precyzyjnych orbit satelitów GNSS z wykorzystaniem mikrofalowych I laseowych pomiarów odległości, 2020)
Based on the Galileo metadata the analytical box-wing model has been composed for theevaluation and absorption of the non-gravitational perturbing forces, i.e., SRP, albedo orEarth’s infrared radiation. The box-wing model can absorb up to 97% of the direct SRPwhereas the rest can be compensated by a set of the estimated empirical parameters. Thisstudy presents the assessment of the non-gravitational perturbing forces acting on the Galileosatellites, as well as indicates the most suitable POD strategy allowing for the determinationof the Galileo orbits with the accuracy of 25 mm in terms of SLR observation residuals.
W wersji elektronicznej dostępne wyłącznie streszczenie rozprawy doktorskiej
Keywords: GNSS; SLR; precise orbit determination; solar radiation pressure; Galileo; wyznaczanie precyzyjnych orbit; bezposrednie promieniowanie słoneczne